Techniques of family guidance in the face of marital and marital problems (Journal Of Educational and Psychological Researches, 2018)
Summary First: The importance of the study and the need for it: The society is composed of an integrated unit of groups and institutions that seek to achieve a specific goal within a system of salary, and the family remains the most influential institutions on the individual and the unity of society, with the roles and responsibilities of the individual and society, and through the continuation and strength of other social organizations derive their ability On the other hand, any break-up in the institution of the family is reflected negatively on the cohesion of society and its interdependence, and the causes of this disintegration vary from society to another, but family problems remain the main factor in obtaining it. Second: Study Objectives : The present study aims to identify; 1-Marital and family problems 2-Causes of marital and family problem. . Family counseling theories 3- . Family extension techniques used to solve family problems 4- Third: Limits of the study ... Fourth: the definition of terminology ... The terms mentioned in the title of the research will be defined Chapter II ... This chapter includes explanation and clarification ... Categories marital and family problems. Causes of marital and family problems. Family counseling theories. Family extension techniques used to solve family problems Chapter III ... Conclusions and recommendations of the research